2014
DOI: 10.1021/ac501998d
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Uranium and Chemical State Analysis of Individual Radioactive Microparticles Emitted from the Fukushima Nuclear Accident Using Multiple Synchrotron Radiation X-ray Analyses

Abstract: Synchrotron radiation (SR) X-ray microbeam analyses revealed the detailed chemical nature of radioactive aerosol microparticles emitted during the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident, resulting in better understanding of what occurred in the plant during the early stages of the accident. Three spherical microparticles (∼2 μm, diameter) containing radioactive Cs were found in aerosol samples collected on March 14th and 15th, 2011, in Tsukuba, 172 km southwest of the FDNPP. SR-μ-X-ray fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
104
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(114 citation statements)
references
References 13 publications
9
104
1
Order By: Relevance
“…Another type of primary radiocesium emission has been reported to consist of glassy, water-insoluble particles with diameters of approximately 2 μm (Adachi et al 2013;Abe et al 2014;Yamaguchi et al 2016) and with high specific activity . These particles are stable at least for a few years in the environment and have recently been found at the ground surface (Satou et al 2016).…”
Section: Possible Host Particles For Radiocesium Resuspensionmentioning
confidence: 99%
“…Another type of primary radiocesium emission has been reported to consist of glassy, water-insoluble particles with diameters of approximately 2 μm (Adachi et al 2013;Abe et al 2014;Yamaguchi et al 2016) and with high specific activity . These particles are stable at least for a few years in the environment and have recently been found at the ground surface (Satou et al 2016).…”
Section: Possible Host Particles For Radiocesium Resuspensionmentioning
confidence: 99%
“…Adachi et al (2013) addressed this sort of contrast in the characteristics of the two plumes' radioactive aerosols in detail, and Abe et al (2014) added more information. They documented the discovery of insoluble, glassy spherules containing radioCs and assumed that the major fraction came from the first event.…”
Section: Estimation Of 90mentioning
confidence: 99%
“…Studies report preferential Cs sorption onto the interlayers (edge sites) both mica and clay-type minerals (Kogure et al, 2012;Mukai et al, 2014;Saito et al, 2014), where it is difficult to disassociate, and is subsequently transported, carried by the host particulate material. Additional studies have also identified Cs within larger material, including 1-2 µm diameter spherical particles (Adachi et al, 2013;Abe et al, 2014;Kogure et al, 2016). Typically employing air-sampling apparatus (located 170 km south west of the facility) in addition to ground-sampled material (tens of kilometers from the plant), some of these studies have also located the existence of uranium species (Martin et al, 2016) within the cores of several of these ejecta fragments (Abe et al, 2014;Kogure et al, 2016).…”
mentioning
confidence: 99%
“…Additional studies have also identified Cs within larger material, including 1-2 µm diameter spherical particles (Adachi et al, 2013;Abe et al, 2014;Kogure et al, 2016). Typically employing air-sampling apparatus (located 170 km south west of the facility) in addition to ground-sampled material (tens of kilometers from the plant), some of these studies have also located the existence of uranium species (Martin et al, 2016) within the cores of several of these ejecta fragments (Abe et al, 2014;Kogure et al, 2016). Whereas some of the material encountered contains actinide species, and others do not, in each instance, the major component of the material analyzed is silicon-constituting the bulk of the material alongside other light and transition elements including C, O, Na, Mg, Al, K, Ca, Fe, and Zn.…”
mentioning
confidence: 99%
See 1 more Smart Citation